Trends and Dynamics of Smart Farming Research in Agricultural Education in Indonesia: A Bibliometric Analysis (2020–2025) - Waworuntu, Juniarny; Ambalao, Shapely (Economics and Digital Business Review, 2026)
Smart farming represents a transformative approach in agriculture, integrating digital technologies, automation, and data analytics to improve productivity, sustainability, and efficiency. This study employs a bibliometric analysis to examine research trends, thematic structures, and influential publications on smart farming within agricultural education in Indonesia from 2020 to 2025. Data were collected from Google Scholar using Publish or Perish and filtered to include 833 peer-reviewed journal articles, which were subsequently analyzed using VOSviewer. The analysis identified four primary thematic clusters: (1) technology-driven systems emphasizing IoT, artificial intelligence, big data, and precision agriculture; (2) capacity-building and community engagement focusing on training, extension programs, and skill development; (3) socio-behavioral and institutional factors affecting technology adoption; and (4) contextual and demographic considerations, including generational differences and situational disruptions. Citation analysis revealed that highly cited studies primarily address human resource competency development, entrepreneurship, and agricultural modernization. The findings indicate a growing research focus on technological innovation, while integration of smart farming into agricultural education curricula remains limited. This study provides insights into current research trends and highlights opportunities for pedagogical innovation and strategic integration of digital agricultural technologies in Indonesia’s agricultural education system